2016
DOI: 10.1155/2016/5472320
|View full text |Cite
|
Sign up to set email alerts
|

GAKG-RGEKG an Epitope That Provokes Immune Cross-Reactivity betweenPrevotellasp. and Human Collagen: Evidence of Molecular Mimicry in Chronic Periodontitis

Abstract: Periodontal disease afflicts 20% of world population. This process usually occurs in the form of being lethargic and chronic, and consequently this disease is known as chronic process. All chronic diseases constantly cause activation of the immune system, and therefore the presentation of microbial peptides which are presented to lymphocytes by professional antigen presenting cells can present microbial peptides very similar to important structures of human economy causing autoimmune diseases, process known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…A similar finding was reported in mouse models of multiple sclerosis and autoimmune diabetes . Furthermore, a number of human studies reported mimicry between gut bacteria and candidate antigens involved in human autoimmune diseases . In line with the notion that specific antigens are being recognized by the immune system, several major histocompatibility complex molecules have been linked to various systemic and ocular autoimmune diseases .…”
Section: Commensal Bacteria and Intraocular Diseasesupporting
confidence: 77%
See 1 more Smart Citation
“…A similar finding was reported in mouse models of multiple sclerosis and autoimmune diabetes . Furthermore, a number of human studies reported mimicry between gut bacteria and candidate antigens involved in human autoimmune diseases . In line with the notion that specific antigens are being recognized by the immune system, several major histocompatibility complex molecules have been linked to various systemic and ocular autoimmune diseases .…”
Section: Commensal Bacteria and Intraocular Diseasesupporting
confidence: 77%
“…[19,20] Furthermore, a number of human studies reported mimicry between gut bacteria and candidate antigens involved in human autoimmune diseases. [21,22] In line with the notion that specific antigens are being recognized by the immune system, several major histocompatibility complex molecules have been linked to various systemic and ocular autoimmune diseases. [23] Specifically, in uveitis, human leukocyte antigen (HLA) complexes have been implicated in disease to include birdshot chorioretinopathy, associated with HLA-A29, [24] Vogt-Koyanagi-Harada disease, associated with HLA-DQw3, [25] and acute anterior uveitis, associated with HLA-B27.…”
Section: Commensal Bacteria and Intraocular Diseasementioning
confidence: 99%
“…Obando-Pereda et al showed that an epitope of Prevotella sp. has high similarity with human collagen report a positive antigen-antibody complex in RA and PD patient's sera [8] ( Table 9).…”
Section: Trojans Against Musclementioning
confidence: 99%
“…Molecular mimicry, term proposed firstly by Damian, is the theoretical probability that exist similarities in the molecular structures (amino acid sequence or conformational structure) between pathogens and the host producing a cross-reactivity immune response turn a defensive immune response into autoimmunity [8,[12][13][14][15][16].…”
Section: Molecular Mimicrymentioning
confidence: 99%
See 1 more Smart Citation